Comparison of Prevalence and Angulation of Impacted Third Molar among Erbil Population with That of Iraq Neighboring Countries - Khurshid Kheder; Hassan Barzanji; Sarkawt Ali (Erbil Dental Journal)
Background and objectives: the problem of impacted teeth remain actual in all countries. Differences in ethnicity, culture and environment may play a role in its occurrence. The objective is to find the differences in prevalence of this problem between population of Erbil/Iraq and Iraqi neighboring countries.